Desempeño laboral de la Hacienda Katherine de la parroquia San Juan - Yepez Morales, Katty Madeley (2020)
The Katherine banana plantation is a private agricultural organization on the San Juan Babahoyo road in the Los Rios province, with 73 productive hectares of bananas, producing jobs for 40 families in the sector. The organization currently seeks to be efficient in terms of competition, senior management must resort to all possible means to meet its goals through a strategic plan, state-of-the-art technology, appropriate logistics, adequate use of its resources, etc., This integrated farm solidly in each of its areas, it has neglected the management of human talent causing inadequate job performance. In the research, the qualitative methodology was used where I help to understand the social phenomenon and its characteristics, the collaborators survey technique was carried out to determine and define a set of actions in order to improve the current situation. For the company, reinforcement and preparation are important in the training of employees, improving processes, product quality and the intellectual level.